As prífrases verbais em português. Algumas incompatibilidades semânticas na construção de um valor aspectual - Hlibowicka-Węglarz, Barbara (Studia Romanica Posnaniensia, 2004)
Verbal periphrases are one of the most representative ways of expression of the category of aspect in the Portuguese language. The purpose of this article is to present how the periphrases compose the aspectual value of expressions. Moreover the author indicates some semantic incompatibilities, which arise between particular elements forming together one periphrase and different elements forming whole expressions.